KONSEP DESAIN RUMAH TINGGAL BERKELANJUTAN DI KOTA MEDAN - Alvan, Syahreza; Novrianty, Irma; Luthan, Putri Lynna A. (Jurnal Sosial Ekonomi Pekerjaan Umum, 2015)
The direction of Medan’s modern development has had a bearing on the practice of construction and architecture. Norms in construction practice have tended to prioritize the immediate physical factors in buildings and often disregard local building rules, lack context with the surrounding environment and create an unfavourable use of space. This study aimed to identify new concepts for community housing in the city of Medan by proposing a planning model based approach to sustainable construction concepts. The method used to develop the model involved a review of diverse literature, analysis of case studies and follow up group discussions. Data were analyzed by descriptive analysis and then discussed in group in order to enrich the study. This allowed a deep exploration of issues and perspectives from professional practitioners, goverment agencies, developers, and economist. The sustainable construction planning model generated by this study provides a comprehensive approach to planning, design, and a system for construction management. The results provide a practical method for planning and design that effectively incorporates sustainable criteria such as; land use, building mass, spatial layout, material selection and construction management. However, there are challenges that must be addressed: capacity and cultural challenges facing the city of Medan in implementing such a model. Nonetheless, this research can be used as a basis to advance practice based research in sustainable planning practice for other cities sharing Medan’s development characteristics.